E3 Quantitative video analysis of cranial and facial movements in huntington’s disease and other movement disorders - Yebenes, Justo Garcia de; Mena, María Angeles; Lopez Sendon, José Luis; Morales, Blas; Fraga, Manuel; Pancorbo, Jesus; Marina, Jose Luis (Journal of neurology, neurosurgery and psychiatry, 2016)
BackgroundRating movement disorders is at best semiquantitative and highly subjective.AimsTo provide an objective and quantitive method for measurement of movement disorders.MethodsPatients and controls were videotaped under standard conditions with smart phones equiped with Android systems and with programs obtained from Mementum, a software tool that measures motor performance in neurological diseases. Mementum connected to the cloud where the algorithms process the data. The tests preloaded were concerned with movement of face, head and neck. This test is performed twice, 1) with the quiet and silent, and 2) with the patient counting. The video takes 24 frames per second (raw signal = 240 pictures). The cloud algorithms separate each frame and compute the differences (number of pixel in the same place and with the same intensities) between every two frames. This process minimises the impact of light, distance to the camera, hair dress or clothes. The outcomes include: a) global movement: it represents the normalised movement average (from 0 = no movement, to 100 = maximal movement); b) displacement in the plane; c) in depth displacement: zooming (near of far) the smart phone camera. Statistical comparison of the results was performed with ANOVA followed by the Fisher’s exact test. Differences were significant when p < 0.05.ResultsWe included 89 subjects in this stydy: Controls, n = 23; HD, n = 43; 50% risk of HD, n = 6; pre-manifested gene carriers of HD, n = 6; PD, n = 10; PSP, n = 2. Twelve patients with HD were taking medications which could decrease craneo-facial movements. Manifest HD patients followed by those with pre-manifested HD had the most movements and PSP the least. Counting increased movements in all groups and increased the differences inter-group. ConclusionsSimple and free applications, in smart phones, provide meaningful data for the evaluation and treatment of patients with HD.